Collective Ijtihad: Regulating Fatwa in Postnormal Times - Shiraz Khan (American Journal of Islam and Society)
In this book, Hossam Sabry Othman examines the relationship between fatwa issuance, maslahah, and the application of collective or deliberative ijtihad (ijtihad jama’i) in the modern context. Othman compares contemporary models of decision-making to traditional mechanisms, as well as analysing the role that jurists (muftis, mujtahids and imams) play in shaping fatwa rulings and final outcomes. While fatwas are technically non-binding, in reality such is the trust and respect that Muslims have for jurists and the institutions that issue them, that they play an important role in shaping Muslim opinion and religious and social norms in the modern context. Othman calls for a reassessment of current institutional practices, contending that Muslim societies need not be vulnerable to the demands of a media driven, technocratic age. Instead, in the interests of a healthy functioning society, the issuance of fatwas should be done in a manner cognizant of the wider modern context, incorporating specialist knowledge, and take in the cultural diversity that exists within the wider ummatic identity. Additionally, for Othman a significant element of the current context is the need to move beyond a simple weighing of matters in terms of their harm and benefits, and to apply the important legal principle of maslahah in a more comprehensive manner that takes into account the maqasid al-shariah in its assessments.